2022
DOI: 10.1038/s41598-022-13242-w
|View full text |Cite
|
Sign up to set email alerts
|

Multiple entrained oscillator model of food anticipatory circadian rhythms

Abstract: For many animal species, knowing when to look for food may be as important as knowing where to look. Rats and other species use a feeding-responsive circadian timing mechanism to anticipate, behaviorally and physiologically, a predictable daily feeding opportunity. How this mechanism for anticipating a daily meal accommodates more than one predictable mealtime is unclear. Rats were trained to press a lever for food, and then limited to one or more daily meals at fixed or systematically varying times of day. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Despite these concerns, a side-by-side comparison of body temperature and FAA in mice on 60% CR vs. 3-h RF showed similar entrainment of activity and body temperature to feeding ( 57 ). Multiple feedings can also be employed: for example, Luby and colleagues demonstrated that mice can anticipate several meals per day but not with high precision while Petersen et al demonstrated that rats are much better at anticipation of multiple mealtimes ( 43 , 58 ).…”
Section: Food Entrainment Methodology In Rodentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite these concerns, a side-by-side comparison of body temperature and FAA in mice on 60% CR vs. 3-h RF showed similar entrainment of activity and body temperature to feeding ( 57 ). Multiple feedings can also be employed: for example, Luby and colleagues demonstrated that mice can anticipate several meals per day but not with high precision while Petersen et al demonstrated that rats are much better at anticipation of multiple mealtimes ( 43 , 58 ).…”
Section: Food Entrainment Methodology In Rodentsmentioning
confidence: 99%
“…Due to their increased size and complexity, many experiments have been completed in rats that would likely not be possible with mice. In a recent study, rats were taught to press a lever for food and then subjected to restricted food access, using lever pressing as a measure of FAA; the lever pressing showed a preprandial increase, even in animals with SCN lesions ( 43 ). Rats have also been shown to be more attuned to entrainment by palatable meals, developing FAA to the presence of a palatable treat provided in addition to standard chow ad libitum ( 44 , 45 ).…”
Section: Model Systems Used To Study Food Entrainmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Since there has been so much difficulty in isolating the neural constituent(s) of FAA, it has been suggested that such a region, referred to as a food entrainable oscillator (FEO), may not exist as a singular entity; therefore lesioning studies may be too narrow of an approach, and the molecular tagging or systems based approaches may offer higher potential in locating multiple FEOs distributed across the brain and body ( Davidson, 2009 ; Mistlberger, 2011 , 2020 ; Nishide et al, 2021 ). The ability of rodents to have multiple bouts of FAA entrained to multiple food deliveries with same or different cycle period further provided evidence that food entrainment is regulated by a multi-core network ( Petersen et al, 2022 ).…”
Section: Food As a Zeitgebermentioning
confidence: 99%